Armigeres subalbatus incriminated as a vector of zoonotic Brugia pahangi filariasis in suburban Kuala Lumpur, Peninsular Malaysia - Muslim, A.; Fong, Mun Yik; Mahmud, Rohela; Lau, Yee Ling; Sivanandam, S. (BMC, 2013)
Background: In 2011, we reported occurrence of natural human infections with Brugia pahangi, a filarial worm of dogs and cats, in a surburb of Kuala Lumpur, the capital city of Malaysia. Our preliminary entomological survey at that time suggested the mosquito species Armigeres subalbatus as the vector of the zoonotic infections. In this present report, we provide biological evidence to confirm our preliminary finding. Findings: A total of 1798 adult female Ar. subalbatus mosquitoes was caught in the vicinity of the suburb, and 1599 were dissected for the presence of filarial larvae. Sixty-two mosquitoes were positive, and 27 of these were infected with L3 larvae. The L3 were inoculated into male gerbils. Microfilariae could be detected in the gerbils 92 days post-infection. Post-mortem on the gerbils recovered adult worms in the peritoneal cavity, heart, lungs, tail and testis. Male adult worms were confirmed to be B. pahangi by the ratio length of their spicules (left spicule: right spicule). Female adult worms were confirmed by the absence of minute cuticular bosses in the tail region. The worms were further confirmed to be B. pahangi by PCR. Conclusions: Our results showed that Ar. subalbatus was the vector for the zoonotic Brugia pahangi infections. This mosquito species should now be categorised as a medically important mosquito species in Malaysia. Its role in the transmission of zoonotic B. pahangi must therefore be considered in future studies on filarial infections.